Social Views or A. Civinskas - Pruskus, Valdas (Problemos, 1994)
The paper deals with the social views and activity of Antanas Civinskas (1876-1913). His evaluation of the growth of antireligious moods and of the spread of socialist ideas in society is analysed. Particular attention is paid to his conception of “national economy”. In the latter the role of rationally organized activity is underlined. The activity is said to be the decisive factor of the growth of economic self-sufficiency and welfare of society.